Association between accelerated biological aging and colorectal cancer: a cross-sectional study - Wang, Sai; Wang, Keyu; Wang, Xiu (Frontiers in Medicine, 2025)
BackgroundBiological age (BA) is regarded as a more accurate marker of aging than chronological age and is commonly used to assess associations with age-related diseases. The relationship between BA measures and the colorectal cancer (CRC) has not yet been investigated.MethodsThis study utilized data from the National Health and Nutrition Examination Survey. BA was quantified using the Klemera–Doubal method age (KDMAge) and phenotypic age (PhenoAge), based on 13 common clinical biomarkers. The prevalence of CRC across quartiles of BA indicators was compared using weighted Chi-square tests. Weighted multivariable logistic regression models were used to assess the association between BA indicators and CRC.ResultsA total of 36,684 participants were included. The weighted prevalence of CRC showed a significant and consistent upward trend across ascending quartiles of chronological age, KDMAge, and PhenoAge, even within gender and age subgroups (all P for trend < 0.05). In the total population and gender subgroups, higher quartiles of PhenoAge acceleration showed a higher weighted prevalence of CRC compared to lower quartiles (P for trend < 0.05). Accelerated PhenoAge was significantly associated with a higher prevalence of CRC (OR = 1.767, 95% CI: 1.236–2.524, P = 0.002). However, accelerated PhenoAge was associated with the increased prevalence of CRC only in individuals older than 65 years (OR = 1.655, 95% CI: 1.143–2.397, P = 0.008).ConclusionBiological aging are positively associated with the prevalence of CRC regardless of gender, particularly among the elderly.